EFFECTIVE METHODS FOR TEACHING WRITING TO B1 LEVEL LEARNERS IN EFL CLASSES - Qurbonova gulzira Olimovna,; Xudoyberdiyeva Laylo Abdumalik qizi,; Mengto'rayeva Shodiya Hamidulla qizi, (Ustozlar uchun, 2025)
Teaching writing to B1 level learners in English as a Foreign Language (EFL) contexts presents unique challenges, including limited linguistic resources and low confidence. This study investigates three teaching methods scaffolded writing tasks, peer feedback, and genre-based instruction to enhance writing proficiency. Conducted over 12 weeks with 20 B1 learners, the intervention resulted in significant improvements in text coherence, grammatical accuracy, and learner confidence. The findings offer practical insights for EFL instructors seeking to foster effective writing skills.